2-(4-Arylbuta-1,3-dien- or 1-en-3-yn-1-yl)chromones as synthons for the synthesis of other nitrogen and oxygen heterocyclic compounds - Albuquerque, Hélio (2015)
It is well known the great biological relevance of oxygen and nitrogen heterocycles. Herein, the reactivity of 2-(4-aryl-1,3-dien- and 1-en-3-yn-1-yl)chromones are explored in order to establish new synthetic routes towards the preparation of new heterocyclic compounds such as xanthones and triazoles. The reactive sites of the starting chromone derivatives (the double and triple bonds) allow them to be involved in reactions such as Diels-Alder and Huisgen cycloadditions. These reactions are used separately or subsequently in order to prepare new biologically active compounds emphasizing the synthetic potential of the referred chromone derivatives. Using these new synthetic routes we were able to develop new compounds, such xanthones bearing triazole moiety, which are expected to enclosure interesting biological properties.